Multiple Directorship & Interlock: An Empirical Study of its Impact on Firms’ Financial Performance - Ahamed, Naseem (Indian Journal of Finance, 2014)
Good and fair corporate governance is the need of the hour. Steady industrialization of the economies is one of the major reasons behind the gradual awareness of investors in good corporate governance practices, as investors in the developed world expect the companies in the developing world to be following the same practices as in their own economy. In the wake of several high profile corporate scandals that broke out in the last few years across the world, and dented the confidence of investors and common shareholders, transparency along with pro investor governance has taken the driver’s seat. An incidence of multiple directorship and interlock of directorship can help increase the level of transparency and fairness in the conduct of companies. Interlock of directorship helps the companies by providing an effective mechanism of scrutinizing companies coupled with the fact that interlock also helps in co-opting external resources, which would be very expensive otherwise. It is also an effective mechanism of increasing the visibility and legitimacy of the relatively new firms. Emerging economies like India provide a unique setting for conducting interlock of directorship research because of the institutional context (comprises of formal rules, informal constraints, and execution characteristics) which is in sharp contrast to its developed counterparts.